Aesthetic Durable Forehead Contouring in Asians With Fat Grafting and Botulinum Toxin. (January 2019) - Kang, Gavin Chun-Wui; Hsiao, Yen-Chang; Huang, Jung-Ju; Chen, Jyh-Ping; Chen, Philip Kuo-Ting; Chen, Yu-Ray; Chang, Chun-Shin
Abstract : Background: Augmentative forehead contouring to create a full rounded smooth forehead is increasingly popular worldwide especially in East Asia where a flat and/or concave irregular forehead is considered unaesthetic. We present our outcomes performing fat transfer to the forehead in combination with botulinum toxin (Botox) corrugator-frontalis injection where indicated in East Asians. Methods: From 2013 to 2017, 62 consecutive patients with flat and/or concave irregular unaesthetic foreheads underwent forehead fat transfer using a microautologous fat transplantation gun. Concomitant Botox injection to minimize corrugator and frontalis contraction-mediated fat displacement was indicated in 23 patients (thin forehead skin and/or excessive forehead animation or rhytides) to prevent forehead vertical crease formation. Thirty-nine subjects with a mean follow-up of 16 months (range = 3–44 months) had their pregraft and postgraft forehead contours assessed on an aesthetic grading scale. Of these 39, 17 completed forehead fat graft volumetric analysis using preoperative and postoperative 3D photography. Results: Aesthetic results were durable at latest follow-up, and all patients were satisfied with their final appearance. The mean amount of fat transferred was 7.72 mL (range = 1.5–33 mL). One subject required a repeat fat grafting (with Botox) because of vertical crease formation after the index procedure (without Botox). Another 12 needed a second fat-grafting session to optimize the contour. All who received Botox did not develop vertical creases. The mean ± SD forehead contour grade improved from 2.29 ± 0.77 to 3.24 ± 0.67 ( P < 0.001). The percentage mean ± SD retention of grafted fat was 46.71% ± 5.77% with Botox versus 39.12% ± 5.24% without Botox ( P = 0.006). Conclusions: Fat grafting to the forehead using our technique with selective Botox administration is an effective, simple, fast, inexpensive, and safe strategy for aesthetic forehead contouring especially for flat and/or concave foreheads. Forehead fat survival rate is objectively improved with simultaneous Botox injection. There is minimum downtime and long-lasting results with high patient satisfaction rates. Abstract : Supplemental digital content is available in the text.